2021
DOI: 10.3390/brainsci11010126
|View full text |Cite
|
Sign up to set email alerts
|

When, How, and to What Extent Are Individuals with Unresponsive Wakefulness Syndrome Able to Progress? Neurobehavioral Progress

Abstract: Accurate estimation of the neurobehavioral progress of patients with unresponsive wakefulness syndrome (UWS) is essential to anticipate their most likely clinical course and guide clinical decision making. Although different studies have described this progress and possible predictors of neurobehavioral improvement in these patients, they have methodological limitations that could restrict the validity and generalization of the results. This study investigates the neurobehavioral progress of 100 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…Patients in MCS and, less frequently, those in VS/UWS can regain full consciousness [4], in some cases even years after the injury [5]. However, a variable but substantial proportion of patients with pDoC (even up to 74%) [4] die within 12 months of brain injury, most often due to severe medical complications such as pneumonia or cardiac failure, with lowest mortality rates following trauma [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients in MCS and, less frequently, those in VS/UWS can regain full consciousness [4], in some cases even years after the injury [5]. However, a variable but substantial proportion of patients with pDoC (even up to 74%) [4] die within 12 months of brain injury, most often due to severe medical complications such as pneumonia or cardiac failure, with lowest mortality rates following trauma [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The selected studies included an overall sample of 2844 patients with disorders of consciousness (eight in coma, 0.3%; 1774 in VS/UWS, 62.4%; 926 in MCS, 32.6%; 136 having emerged from MCS [eMCS], 4.7%) caused by different aetiologies (traumatic brain injury 992, 34.9%; non‐traumatic brain injury 1852, 65.1%), with a mean age of 48 years (not available in two studies); 1825 (64.2%) patients were male (not available in one study). Most studies [3, 5, 13–19, 21, 23, 24, 26, 31, 32, 35, 36, 39, 40] investigated the prognostic role of demographic, clinical and anamnestic factors. Some studies also included neurophysiological [5, 16, 19, 20, 22, 23, 25, 28, 30, 32, 33, 38] or neuroimaging [15, 26, 29, 37–39] investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the included studies are reported in Table S1. Most studies [3,5,14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] enrolled patients in Europe (23/30, 77%), whereas five studies [15,[36][37][38][39] (16%) included patients from China, and two studies [13,40] (7%) included patients from the Americas.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…No obstante, el pronóstico de pacientes traumáticos sí es mejor, aunque la evidencia es de confianza baja a moderada en poblaciones adultas y pediátricas (17). Noé et al (18) siguieron a cien pacientes con síndrome de vigilia sin respuesta durante 132 +/-85 días, encontrando que cerca de un tercio de los pacientes progresaron hacia un estado de consciencia mínima y cerca de un décimo de ellos emergieron de este estado.…”
Section: Historia De Terriunclassified